Is it green? Designing a blockchain-based certification system for the EU hydrogen market - Schmid, Jonathan; Ubacht, Jolien; van Engelenburg, Selinde; van Oudheusden, Jan; Chappin, Emile (Frontiers in Blockchain, 2024)
Energy production and consumption are major contributors to Greenhouse Gas (GHG) emissions, exacerbating one of the major challenges of modern societies: climate change. Thus, societies must switch to more sustainable energy sources. Green hydrogen emerges as a promising alternative energy carrier, facilitating storage and utilization across various industries. However, amidst different production processes, solely sustainable electrolysis stands out as an environmentally benign production method. Hydrogen producers must prove provenance and sustainable production to regulatory bodies and hydrogen buyers to comply with the regulations for sustainable development. Blockchain provides a viable solution encompassing trustworthy and secure information sharing between untrusted partners. In this article, we employ a design science research approach to develop a blockchain-based certification system (BLC-CS) for green hydrogen. Through collaboration with experts in both gathering requirements and evaluation, we design an artifact that streamlines the certification process for producers, regulators, and consumers. Our proposed solution facilitates information gathering, verification, and reporting, contributing to the advancement of sustainable energy practices. We provide a comprehensive discussion of the BLC-CS's feasibility for green hydrogen certification including technical extensions, recommendations for practitioners, and directions for future research.